Water Balance Prediction by Simulating Land Use Planning and Water Retention Infrastructure in Upper Cisadane Sub-Watershed, West Java, Indonesia - Hidayat, Yayat; Rachman, Latief Mahir; Wahjunie, Enni Dwi; Baskoro, Dwi Putro Tejo; Purwakusuma, Wahyu; Yusuf, Sri Malahayati; Araswati, Fulki Dwiyandi (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2024)
Currently, water resources management is still focused on on-site water resources infrastructure to achieve optimal water utilization, with almost never considered land management in which water resources are produced naturally. The research aim is to study the water balance in the Upper Cisadane Sub-Watershed, and to simulate a land use plan and development of water resource infrastructure to fulfill the need for water in the Upper Cisadane Sub-Watershed using the SWAT (Soil and Water Assessment Tool) model. Existing water availability was calculated using stream discharge data from River Flow Measurement Station Empang, whereas water demand has been analyzed for domestic, industries, agriculture, fisheries, and animal husbandry. Totally, water availability in the Upper Cisadane Sub-Watershed was ± 222.9 MCM (Million Cubic Meters) year-1, which was higher than the demand for water of as much as ± 209.8 MCM year-1 and resulted in a water surplus of ± 13.1 MCM year-1. However, water availability was not evenly distributed throughout the year, and there was always a water deficit in the dry season. To overcome drought during the dry season, five simulations of land use management and construction of water retention infrastructure were carried out using the SWAT model. The water deficit in the Upper Cisadane SubWatershed will be overcome by the consistent application of the spatial plan of West Java Province, reforestation of converted forest areas, applied agroforestry in agricultural land, and development of a reservoir with a storage capacity of 30 MCM.